Outcomes of trans-anal natural orifice specimen extraction combined with laparoscopic anterior resection for sigmoid and rectal carcinoma: An observational study. Issue 38 (September 2018) - Ng, Hoi-Ioi; Sun, Wu-qing; Zhao, Xiao-mu; Jin, Lan; Shen, Xi-xi; Zhang, Zhong-tao; Wang, Jin
Abstract : Abstract: Colorectal carcinoma is currently the third most frequent cancer worldwide. Conventional open surgery was replaced by laparoscopic anterior resection with total mesorectal excision for the treatment of sigmoid and rectal carcinomas; however, it needed an incision to harvest the specimen, which contributed to complications. In 2013, trans-anal natural orifice specimen extraction laparoscopic anterior resection (Ta-NOSE-LAR) to treat sigmoid and rectal carcinoma was performed in our hospital for the first time. The aim of this study was to investigate the outcomes of Ta-NOSE-LAR in sigmoid and rectal carcinoma. Seventy-three patients diagnosed with sigmoid and rectal carcinoma were enrolled between September 2013 and June 2016. Thirty-five patients underwent Ta-NOSE-LAR, whereas the others underwent traditional laparoscopic anterior resection (LAR). We compared the operative data, postoperative complications, pathological evaluation results, and incision-related complications between the 2 groups. Our result showed that the operative time, specimen length, tumor size, amount of total lymph nodes, and lymph node metastasis between the 2 groups were not statistically different. Further, without abdominal scaring for harvesting the specimen, the operative blood loss (49.29 ± 14.63 vs 69.29 ± 13.54 mL, P < .001) and post-operation hospital stay (5.77 ± 0.94 vs 6.76 ± 0.75 days, P < .001) of the Ta-NOSE-LAR group were less than those of the LAR group. Besides, the follow-up data showed that 2 patients were lost to follow-up, and 1 patient had liver metastasis 2 years after surgery in the LAR group, whereas the others showed no regional recurrence, distant metastases, or critical complications. Ta-NOSE-LAR is a valuable and alternative surgical method to treat sigmoid and rectal carcinoma, with the advantages of being a scarless procedure and having a lower post-operation hospital stay duration.